TOM PAULIN'S POETRY OF TROUBLES - Wolwacz, Andrea Ferras (Organon, 2019)
This paper is part of my PhD thesis. It examines contemporary Northern Irish Literature written in English with the help of the theoretical approach of Irish Studies. It aims to introduce and make a critique of poetry written by Tom Paulin, a contemporary British poet who is regarded one of the major Protestant Irish writers to emerge from Ulster province. The thread pursued in this analysis relates to an investigation of how ideological discourses and the issues of identity are represented in the poet’s work. The author’s critical evaluation of existing ideologies and identities and his attempt to respond to them will also be analyzed. Four poems from three different collections are investigate. Paulin’s poems function as testimonies, denouncement and criticism of the Irish history.